Guinea : Financial Sector Stability Review. (IMF Staff Country Reports; Country Report, 2020)
The IMF conducted a Financial Sector Stability Review of the Republic of Guinea in June 2019. The review shows that while the current economic situation is benign, the financial soundness indicators (FSIs) point to increasing vulnerabilities. The economic outlook is currently positive. Moreover, financial inclusion is growing rapidly as mobile money services are quickly adopted. However, the FSIs suggest growing vulnerabilities and possibly some idiosyncratic stress in the banking sector. As a result of data quality and availability issues, it is difficult to make a more in-depth assessment of financial stability and potential vulnerabilities. The financial sector structure is, to some extent, a mitigant to the potential financial stability vulnerabilities. All banks are part of foreign financial groups that they can fall back on during periods of stress. While the current economic situation is benign, it is an opportune moment to develop the necessary capacity to handle potential financial stability vulnerabilities. As a priority, on and offsite supervision and the availability and quality of data on the banking sector, and in a later stage also for the other financial sectors, should be significantly improved, and the regulatory framework for banks should be modernized.